2014
DOI: 10.5012/bkcs.2014.35.4.1165
|View full text |Cite
|
Sign up to set email alerts
|

Improved Energy Conversion Efficiency of Dye-sensitized Solar Cells Fabricated using Open-ended TiO2Nanotube Arrays with Scattering Layer

Abstract: We prepared dye-sensitized solar cells (DSSCs) with enhanced energy conversion efficiency using open-ended TiO 2 nanotube arrays with a TiO 2 scattering layer. As compared to closed-ended TiO 2 nanotube arrays, the energy conversion efficiency of the open-ended TiO 2 nanotube arrays was increased from 5.63% to 5.92%, which is an enhancement of 5.15%. With the TiO 2 scattering layer, the energy conversion efficiency was increased from 5.92% to 6.53%, which is an enhancement of 10.30%.After treating the open-end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…However, when the levels of thickness were compared, the bottom wall (~35 nm) was much thicker than the top wall of the freestanding TiO 2 nanotube arrays. In previous works [ 18 , 25 , 26 , 27 , 28 , 29 , 30 ], we reported that the shape of TiO 2 nanotube arrays prepared by anodization were likely to be a corn shape type and that the thicker bottom layer disturbed the electron transport and electrolyte diffusion. Therefore, we suggested that the removal of the bottom layer would facilitate better energy conversion efficiency in DSSCs.…”
Section: Resultsmentioning
confidence: 96%
“…However, when the levels of thickness were compared, the bottom wall (~35 nm) was much thicker than the top wall of the freestanding TiO 2 nanotube arrays. In previous works [ 18 , 25 , 26 , 27 , 28 , 29 , 30 ], we reported that the shape of TiO 2 nanotube arrays prepared by anodization were likely to be a corn shape type and that the thicker bottom layer disturbed the electron transport and electrolyte diffusion. Therefore, we suggested that the removal of the bottom layer would facilitate better energy conversion efficiency in DSSCs.…”
Section: Resultsmentioning
confidence: 96%
“…However, by using a physical method such as ion milling, the barrier layer can be removed without any damage to the TNTAs. 27 To increase the ECE in the DSSCs, the barrier layer of the freestanding TNTAs was removed by an ion milling method. The resulting TNTAs are called “open-ended freestanding TNTAs” and are shown in Figure 1c.…”
Section: Resultsmentioning
confidence: 99%
“…The sintered layers were then immersed in 40 mM of TiCl 4 aqueous solution at 70 °C for 30 min and sintered again at 500° C for 40 min to obtain the TiO 2 reflector layer and to increase the surface area of the TiO 2 layer. So it will be able to improve the absorption of the dye and implies the optimization of the light harvesting [13].…”
Section: A Materialsmentioning
confidence: 99%